Seismic Behavior of One-Storey Gabion-Box Walls Buildings - Samayoa, Julio; Baraccani, Simonetta; Pieraccini, Luca; Silvestri, Stefano (Frontiers in Built Environment, 2018)
Gabion-boxes, made with steel wire mesh and filled with stones of appropriated size, are normally stacked up one into another to form a retaining wall. Given their reduced costs and the easy availability of their constituting materials, gabion-box walls have been extensively used in developing countries (such as Nepal) also to realize simple one-storey residential buildings. In recent years, many of these structures have been subjected to several strong earthquakes and have shown a good seismic behaviour, even if they have never been the object of a proper structural design. In the scientific literature, research studies have been developed on gabion-box walls used as retaining systems, but no investigations have been conducted on the performances of gabion-box walls buildings. In this respect, the general objective of this research work is to give a first insight into the static and seismic behaviour of such gabion-box walls buildings through analytical considerations and numerical models. In detail, with reference to a typical 5 m x 5 m plan model, this paper investigates the in-plane and out-of-plane seismic responses of its constituting walls, by means of simple analytical interpretations and Discrete Element Method (DEM) numerical simulations. Even if this study should be considered as a starting point and even if the fundamental cellular behaviour of the 3-dimensional structure has not been fully taken into account, some criticalities have been disclosed and the order of magnitude of the seismic activation load multipliers has been estimated. The out-of-plane collapse mechanism is characterised by multiplier around 0.15, whilst the in-plane mechanism multiplier depends on the position of the door in the single wall (0.10 – 0.20), but can be easily increased with lintel beams placement. The results are based on the assumptions taken by several authors and have not been verified with experimental tests. Nevertheless, some practical suggestions (basically in terms of spacing and construction details, such as vertical connectors and reinforcing steel knots) can be derived to improve the construction in order to ensure a better seismic behaviour.